Studying Autism in Rodent Models: Reconciling Endophenotypes with Comorbidities - Argyropoulos, Andrew; Gilby, Krista; Hill-Yardin, Elisa L. (Frontiers in Human Neuroscience, 2013)
Autism spectrum disorder (ASD) patients commonly exhibit a variety of comorbid traits including seizures, anxiety, aggressive behavior, gastrointestinal problems, motor deficits, abnormal sensory processing and sleep disturbances for which the cause is unknown. These features impact negatively on daily life and can exaggerate the effects of the core diagnostic traits (social communication deficits and repetitive behaviors). Studying endophenotypes relevant to both core and comorbid features of ASD in rodent models can provide insight into biological mechanisms underlying these disorders. Here we review the characterization of endophenotypes in a selection of environmental, genetic and behavioural rodent models of ASD. In addition to exhibiting core ASD-like behaviours, each of these animal models display one or more endophenotypes relevant to comorbid features including altered sensory processing, seizure susceptibility, anxiety-like behaviour and disturbed motor functions, suggesting that these traits are indicators of altered biological pathways in ASD. However, the study of behaviours paralleling comorbid traits in animal models of ASD is an emerging field and further research is needed to assess altered gastrointestinal function, aggression and disorders of sleep onset across models. Future studies should include investigation of these endophenotypes in order to advance our understanding of the etiology of this complex disorder.